Analisis Kegiatan Employee Relations PT Bank Central Asia Tbk Kantor Cabang Pembantu Juanda Bekasi Dalam Memberdayakan Kompetensi Komunikasi Pelayanan CXO : Analisis Kegiatan Employee Relations PT Bank Central Asia Tbk Kantor Cabang Pembantu Juanda Bekasi Dalam Memberdayakan Kompetensi Komunikasi Pelayanan CXO - Melly Agustin; Robbikal Muntaha Meliala; Teguh Tri Susanto (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to analyze the role of employee relations (ER) in empowering the communication competence of customer experience officers (CXO) at PT Bank Central Asia Tbk, Juanda Bekasi Sub-Branch Office. The main focus of this research is on how employee relations (ER) activities support the enhancement of interpersonal communication skills, which are essential in maintaining the quality of digital banking services. This research employed a qualitative approach with a descriptive method. Data were collected through participatory observation and in-depth interviews with employee relations (ER) supervisors, customer experience officers (CXO), and customers. Data analysis was conducted using an interactive model consisting of data reduction, data presentation, and conclusion drawing. The findings reveal that employee relations (ER) significantly contribute to improving the confidence, mental readiness, empathy, and communication skills of customer experience officers (CXO). The positive impact of these activities is not only experienced by employees internally but also perceived by customers through more friendly, humanistic, and professional services. Therefore, employee relations (ER) can be positioned as a strategic partner in supporting the success of digital banking services while simultaneously strengthening the company’s positive image in the public eye.